Efficacy of modified active physical therapy program on pain, muscle strength, and function in adolescent football players with osteitis pubis - Waleed S. Mahmoud; Marwa M. Ibrahim; Nadia L. Radwan (Bulletin of Faculty of Physical Therapy, 2024)
Abstract Background In athletes, osteitis pubis (OP) is considered a major cause of chronic groin pain. In addition to the difficulties with diagnosis, controversy exists regarding the most appropriate treatment approach. The study aimed to evaluate the effect of a modified active physical therapy program (MAPT) on pain, hip and trunk muscle strengths, and lower extremity function in adolescent football players with OP. Methods Fifty football players aged from 12 to 18 years with OP were included and allocated into two groups: the MAPT group (n = 24) and the traditional physical therapy (TPT) group (n = 26). Each group received a different treatment protocol for 60 min applied 3 times/week for 12 weeks. A visual analog scale, digital hand-held dynamometer (HHD), and lower extremity functional scale (LEFS) were used to measure pain, hip and trunk muscle strengths, and lower limb function, respectively, at baseline and 12 weeks post-intervention. Results There was a highly significant difference in the TPT group’s pain score (p < 0.001) compared with the MAPT group. Also, the strength of hip flexors, abductors, adductors, internal rotators, external rotators, and trunk flexors and extensors improved significantly (p < 0.05) than the TPT group. However, the between-group analysis revealed that the strength of hip extensors and LEFS in the MAPT group achieved a highly significant difference (p < 0.001) compared with the TPT group. Conclusion MAPT could be recommended strongly in the rehabilitation of OP in adolescent football players in which the functional abilities of OP patients improved because of reduced pain levels and increased hip and trunk muscle strength. (IRCT20210909052421N3, Iranian Registry of Clinical Trials, https://www.irct.ir/trial/68946/pdf , 9-April-2023).